Analisis Kadar Parasetamol dan Kafein Dalam Sediaan Tablet Menggunakan Metode Spektrofotometri Derivatif Zero Crossing - Rosaldi, Hikmah; Pulungan, Ainil Fithri; Ridwanto, Ridwanto (Universitas Negeri Gorontalo, 2025)
The development of drugs in the form of combination tablets at this time has increased a lot; combining drugs in a tablet preparation can provide an increasing reaction and ability. This makes combining drugs such as Paracetamol and caffeine an effective combination in the pharmaceutical field. Paracetamol is an antipyretic analgesic drug that can be combined with caffeine which can be used in therapy with a combination of these drugs. The objective of this research was to ascertain the concentration of a combination of paracetamol and caffeine in a tablet formulation by employing a zero cross-derivative spectrophotometric method. In this study, solvent optimization was carried out with 17 categories of solvent selection, and acetate: methanol (30:70) was selected using the zero cross-derivative methods with a dA / d plot utilizing the maximum wavelength of paracetamol 258 nm and caffeine 288 nm, because there was an actual wavelength shift in this analysis. To validate the determination of the level of the zero cross-derivative method using the second absorption in the ace solvent (30:70 acetate: methanol). Spectrophotometric analysis of zero crossing derivatives of a mixture of paracetamol and caffeine found that paracetamol levels in tablet A were 95.24 8.47%, in tablet B of 92.86 0%, and in tablet C of 96.5 0%, while the caffeine content was 104.89 0%, 102.09 0%, and 91.6 0%. According to USP 30 NF 25 (2007), it can be concluded that the test results of the composition of paracetamol and caffeine in tablets meet the requirements.